FAO fisheries technical paper; N387 - P V. G. K Reddy (FAO, 1999)
The book includes information on spawning behaviour and breeding under natural and culture conditions, distribution, genetic characterization, status of gentic resources, conservation efforts and hybridization among Indian major carps and with other cyprinids.